179k views
1 vote
-p + 4p = 6 prob the last one for now i think

User Kuurde
by
6.1k points

2 Answers

4 votes

Answer:

p=2

Explanation:

add -p to 4p and you get 3p

then divide both sides by 3 to get p alone so you get p=2 bc 6/3=2

User Tom Faltesek
by
5.6k points
1 vote

Answer:

p = 2

Explanation:

First, simplify:

3p = 6

Then, divide 3 on both sides:

p = 2

Hope this helps ^^

User Enno Shioji
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.